Swiss Public Administration Making the State Work Successfully - Ladner, Andreas; Soguel, Nils; Emery, Yves; Weerts, Sophie; Nahrath, Stéphane (Governance and Public Management, 2019)
Swiss citizens approve of their government and the way democracy is practiced; they trust the authorities and are satisfied with the range of services Swiss governments provide. This is quite unusual when compared to other countries. This open access book provides insight into the organization and the functioning of the Swiss state. It claims that, beyond politics, institutions and public administration, there are other factors which make a country successful. The authors argue that Switzerland is an interesting case, from a theoretical, scientific and a more practice-oriented perspective. While confronted with the same challenges as other countries, Switzerland offers different solutions, some of which work astonishingly well. Andreas Ladner is Professor for Political Institutions and Public Administration at the Institut de Hautes Études en Administration Publique (IDHEAP) at the University of Lausanne, Switzerland. His research interests include the quality of democracy, political institutions and public administration, local government, political parties and voting advice applications. Nils Soguel is Professor of Public Finance at the Institut de Hautes Études en Administration Publique at the University of Lausanne, Switzerland. His research interests include public sector financial management, fiscal policy, fiscal federalism and the evaluation of non-market goods and services. Yves Emery is Professor for Public Management and Human Resource at the Institut de Hautes Études en Administration Publique at the University of Lausanne, Switzerland. His areas of research include HRM strategies, work identities, motivation and competencies of civil servants and public managers. Sophie Weerts is Associate Professor of Public Law at the Institut de Hautes Études en Administration Publique at the University of Lausanne, Switzerland. Her research interests are in constitutionaland administrative law. They focus on the structural sources and transformation of public law and the separation of powers. She also works on human rights, language policies and gender policy. Stéphane Nahrath is Professor of Public Policy at the Institut de Hautes Études en Administration Publique at the University of Lausanne, Switzerland. His areas of research include comparative public policy, sustainable resource management and circular economy.